Clinico-Epidemiological Profile of Intracerebral Hemorrhage - Modi, Tejas N; Santosh, S A; Dhoreeyanee, Falgun K; Patil, Pankaj S (National Journal of Community Medicine, 2017)
Introduction: Clinico-epidemiological spectrum plays key role in provisional diagnosis and prognosis of Intracerebral Hemorrhage (ICH). The objectives of this study were to evaluateclinico-epidemiological profile and to identify and analyze clinical determinants of In-hospital mortality. Material and Methods: All patients (n=211), aged more than 12 years, diagnosed with ICH (based on CT scan/MRI) were studied for demographic profile, clinical profile, Glasgow Coma Scale (GCS) on admission and outcome. Results: ICH was more common in >60 yr age group (52.13%). Mean Age (±SD) is 62.04 (±15.16). M: F ratio is 1.15:1. Its incidence increased during the winter season (53.55%) from the months of November to February and early morning hours (61.14%). Weakness (69.67%) and Loss of consciousness (LOC) /altered sensorium (59.72%) were the two most common presenting complaints on admission. In-Hospital mortality was 87(41.23%) with maximum mortality occurring within 72 hours. Conclusion: In-hospital clinical mortality determinants of ICH on admission were: Loss of consciousness (LOC)/altered sensorium, headache, vomiting, addiction, tobacco, smoking, hyperglycemia, MAP >120, and GCS ≤ 8.